Comparative study between fast and slow induction of propofol given by target-controlled infusion: expected propofol concentration at the effect site. Randomized controlled trial - Simoni,Ricardo Francisco (2015)
BACKGROUND AND OBJECTIVE: Studies have shown that the rate of propofol infusion may influence the predicted propofol concentration at the effect site (Es). The aim of this study was to evaluate the Es predicted by the Marsh pharmacokinetic model (ke0 0.26 min-1) in loss of consciousness during fast or slow induction. METHOD: The study included 28 patients randomly divided into two equal groups. In slow induction group (S), target-controlled infusion (TCI) of propofol with plasma, Marsh pharmacokinetic model (ke0 0.26 min-1) with target concentration (Tc) at 2.0-µg mL-1 were administered. When the predicted propofol concentration at the effect site (Es) reached half of Es value, Es was increased to previous Es + 1 µg mL-1, successively, until loss of consciousness. In rapid induction group (R), patients were induced with TCI of propofol with plasma (6.0 µg mL-1) at effect site, and waited until loss of consciousness. RESULTS: In rapid induction group, Tc for loss of consciousness was significantly lower compared to slow induction group (1.67 ± 0.76 and 2.50 ± 0.56 µg mL-1, respectively, p = 0.004). CONCLUSION: The predicted propofol concentration at the effect site for loss of consciousness is different for rapid induction and slow induction, even with the same pharmacokinetic model of propofol and the same balance constant between plasma and effect site.